Aminopotassiation by Mixed Potassium/Lithium Amides: A Synthetic Path to Difficult to Access Phenethylamine Derivates. Issue 50 (8th October 2020) - Seymen, Andreas; Opper, Ulrike; Voß, Andreas; Brieger, Lukas; Otte, Felix; Unkelbach, Christian; O'Shea, Donal F.; Strohmann, Carsten
Abstract: Insights gained from a comparison of aminometalation reactions with lithium amides, potassium amides and mixed lithium/potassium amides are presented. A combination of structural characterization, DFT calculations and electrophile reactions of aminometalated intermediates has shown the advantages of using a mixed metal strategy. While potassium amides fail to add, the lithium amides are uncontrollable and eliminated, yet the mixed K/Li amides deliver the best of both systems. Aminopotassiation proceeds to form the alkylpotassium species which has enhanced stability over its lithium counterpart allowing for its isolation and thereby its further characterization. Abstract : The use of a mixed‐metal system consisting of LiNR2 /KOR increases the selectivity of the aminometalation of styrene derivatives in favour of a potassiated intermediate over a polymerization product. Crystal structures along with quantum chemical calculations and experimental investigations demonstrate the additional advantages of potassium over lithium or sodium for the stability of metalated phenylethylamines.